LITERATURE REVIEW: EFEKTIFITAS TEMULAWAK (CURCUMA XANTHORRIZA ROBX) TERHADAP PENINGKATAN BERAT BADAN PADA ANAK - Raziansyah Raziansyah (Journal of Nursing Invention, 2020)
Background: In Indonesia, the prevalence of malnutrition and malnutrition in children is 19.6%, this is a big challenge that requires attention in increasing food consumption in children, as an indicator of which is bodyweight. One way is to consume herbal Jammu, namely ginger, which is empirically widely used as a single or mixed medicine to increase appetite and body weight. The Purpose: Of this study was to find the effectiveness of ginger (curcuma xanthorriza robx) on weight gain in children. Methods: The database was collected through google scholar search, data was collected in the period 2015-2020 with research inclusion criteria with children under 9 years of age as respondents. Result: date obtained from 3 articles from 53 search results. Conclusion: Temulawak rhizome is the main ingredient for traditional medicine. Efficacy of ginger empirically as an increase in appetite activity and children's body weight, besides that Curcuma, can also increase the immune system, Temulawak also has pharmacological effects of active substances as an anti-inflammatory (anti-inflammatory) and inhibits edema (swelling).